Marmalade’s formulation of Madu Susu Orange (Citrus reticulata) on multiple concentrations of sucrose [Formulasi marmalade jeruk madu susu (Citrus reticulata) pada berbagai konsentrasi sukrosa] - Agustina, Mulya; Dewi, Yohana Sutiknyawati Kusuma; Lestari, Oke Anandika (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
Generally, the type of orange used in marmalade production is Sunkist oranges. In this study, Madu Susu Oranges (Citrus reticulata), a local orange variety typically consumed fresh and rarely processed into products, were used as the raw material for making marmalade. Additionally, sucrose is a key ingredient that can influence the balance between pectin and water in marmalade, affecting its characteristics and making it a valuable topic for further research. The main objective of this research was to determine the best sucrose concentration in the Madu Susu Orange marmalade formulation based on its physicochemical and organoleptic characteristics. The research design used was a Randomized Block Design, one factor of the sucrose concentration level (75%, 80%, 85%, 90%, and 95%) in 5 repetitions. The data were analyzed using ANOVA and further tested with the HSD test at a 5% significance level. The determination of the best treatment was conducted using the effectiveness index method. The results showed that the best treatment was at a 95% sucrose concentration with a 0.77 treatment value (TTV). The physicochemical and sensory characteristics of the Madu Susu Orange marmalade at 95% sucrose concentration were: total acidity of 0.52%, pH 5.82, total soluble solids of 68.00%, moisture content of 20.87%, and color values L* 29.94, a* 9.87, b* 49.90. Sensory test results for the best treatment were color 3.80 (liked), texture 3.67 (liked), and taste 4.17 (very liked).